Parameters of the Influenza Epidemic in Russia in the 2019-2020 Season - L. S. Karpova; T. P. Stolyarova; N. M. Popovtseva (Эпидемиология и вакцинопрофилактика)
Relevance. The National influenza center uses additional criteria: baselines and thresholds for epidemic intensity for early recognition of the onset and assessment of epidemic intensity. Aim. To characterize the parameters of the flu epidemic in the Russian Federation in the 2019-2020 season and assess the intensity of the last 2 epidemics and the effectiveness of baselines and intensity thresholds. Materials and methods. The database of the research Institute of influenza on weekly morbidity, hospitalization, deaths from influenza and ARVI in the cities-reference bases of the National center for influenza was used. The analysis of the flu situation is based on comparing the current incidence of influenza and ARVI with weekly epic thresholds and baselines. A comparative assessment of the intensity of the last 2 influenza epidemics was carried out using intensity thresholds calculated by the moving epidemic method (MEM). Results. The main parameters of the 2019-20 influenza epidemic compared to the previous one are described. There was an increase in the incidence of clinically diagnosed «fluenza» in the pre-epidemic period and the early onset of both epidemics and reaching a peak in the 6th calendar week. This season, the epidemic started among school children, then among adults, and in the past-among the adult population, the incidence of children 0-2 years old was below the thresholds in both epidemics. This season, the average duration of the epidemic and the incidence in cities were higher among school children and adults, and over the entire period of the epidemic, the incidence was higher in all age groups across the country. This season, the epidemic started in the North Caucasus Federal district, its intensity was medium and low, in the past - it started simultaneously in the Siberian, Ural and North Caucasus districts, and its intensity was very high (in the North Caucasus) and high (in the Siberian Federal district) and the average level of 6 districts. The intensity and duration of epidemics were higher in districts with an early onset (in the North Caucasus and Siberian Federal districts). Both epidemics in the country were of moderate intensity, but there were fewer deaths from influenza in the last epidemic. Conclusion. Comparative characteristics of epidemics using baselines and intensity thresholds allowed us to identify the features of the epidemic process in the seasons 2018-19 and 2019-20: the earlier onset of both epidemics; a noticeable increase in the incidence of fluenza before the beginning of epidemics; a decrease in the intensity of epidemics and mortality from influenza; features of the epidemic process in Federal districts. The effectiveness of using additional criteria in the analysis of the influenza epidemic in Russia and this season has been confirmed. In both epidemics, the weekly epidemic thresholds for influenza and ARVI were more sensitive when determining the start of the epidemic, and the end of it, on the contrary, were baselines, and the baselines of morbidity and hospitalization with a diagnosis «influenza» determined the beginning and end of the epidemic even more precisely.